Magnetic iron oxide nanomaterials: A key player in cancer nanomedicine. Issue 3 (21st July 2020) - Liang, Chen; Zhang, Xinglin; Cheng, Zijin; Yang, Mengsu; Huang, Wei; Dong, Xiaochen
Abstract: Magnetic iron oxide nanomaterials are among the most widely studied candidates for cancer nanomedicine, because of not only their great biocompatibility and abundance of raw materials, but also their diverse physicochemical properties and biological effects. Represented by magnetite and maghemite, various iron oxide‐based magnetic nanomaterials have been developed for cancer diagnosis and treatment. This mini review presents an up‐to‐date overview of magnetic iron oxide‐based cancer nanomedicines with an emphasis on bioimaging and therapy. Abstract : Magnetic iron oxide nanomaterials (MIONs) belong to the most widely studied candidates for cancer nanomedicine because of their biocompatibility, abundant raw materials, and especially, their diverse physicochemical properties and biological effects. This mini review presents an up‐to‐date overview of MIONs‐based cancer nanomedicines with an emphasis on bioimaging and therapy.